PENGGUNAAN METAFORA DALAM LAYLA MAJNUN - Suharsono Suharsono (Sunan Kalijaga State Islamic University Yogyakarta, 2014)
The study of the metaphor in a literary work can be used to find out the author’s creativity in utilizing words to concretize an abstraction through the use of metaphor. Because every human being is essentially unique, each author is assumed to have his/her own style in creating metaphors. The two questions in this article are: 1) how is the typical form of metaphor in Layla Majnun as the embodiment of creativity? ; 2) what is the function of the use of metaphor in Layla Majnun? Based on the analysis of data, a metaphor can be classified into a phrase, clause, and sentence. At the phrasal level, position or location of the image element can be either in the beginning or in the end of the topic. Meanwhile, at the level of the clause and sentence, image elements are always in the end of the topic. This latter sequence is possible because the clause part of the “explained or described” is filled syntactically by the predicate. The predicate in Indonesian is predominantly located after the subject. The study of the use of metaphor in Layla Majnun leads to the conclusion that the creativity of the author in creating metaphor reflected on how human (the author) sees the world. Because human perception is inseparable from the environment in which the author lives, develops, and interacts, the use of metaphor in Layla Majnun reflects an overview of the social life, values of culture, and customs of the Arab people at that time.